CHILDREN’S OPPRESSION TOWARD ENDER FROM ENDER’S GAME NOVEL - Sofyan, Fitria; Kuncara, Singgih Daru; Asanti, Chris (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
ABSTRACT This study is focused on the children’s oppression experienced by Ender as the main character in a novel entitled Ender’s Game. The novel tells about a child who was training under an army to fight aliens. The research question of this study is what types of oppression that Ender has to experience as portrayed in Ender’s Game novel using Young’s five faces of oppression theory. Under the paradigm of qualitative research design, the findings are descriptively explained. The result of the analysis using Young’s theory showed that Ender experienced three types of oppression. In the total of nine data found, they were classified under violence, cultural imperialism, and powerlessness. Four data found were under violence, three data belonged under cultural imperialism, and two data classified under powerlessness. Lastly, based on the findings, it can be concluded that novel as part of literary work can also function as a reminder and a tool to improve awareness to society about the issues that are still happening. Key words: oppressor, oppression, Ender’s Game novel ABSTRAK Kajian ini difokuskan pada penindasan anak-anak yang dialami oleh Ender sebagai tokoh utama dalam novel berjudul Ender's Game. Novel tersebut menceritakan tentang seorang anak yang sedang berlatih di bawah pasukan untuk melawan alien. Pertanyaan penelitian dari studi ini adalah jenis penindasan apa yang harus dialami Ender seperti yang digambarkan dalam novel Ender's Game menggunakan teori lima wajah penindasan Young. Di bawah paradigma desain penelitian kualitatif, temuan dijelaskan secara deskriptif. Hasil analisis menggunakan teori Young menunjukkan bahwa Ender mengalami tiga jenis penindasan. Dari total sembilan data yang ditemukan, mereka diklasifikasikan dalam kekerasan, imperialisme budaya, dan ketidakberdayaan. Empat data ditemukan berada di bawah kekerasan, tiga data milik imperialisme budaya, dan dua data diklasifikasikan dalam ketidakberdayaan. Terakhir, berdasarkan temuan tersebut dapat disimpulkan bahwa novel sebagai bagian dari karya sastra juga dapat berfungsi sebagai reminder dan alat untuk meningkatkan kesadaran masyarakat tentang isu-isu yang masih terjadi. Kata kunci: penindas, penindasan, novel Ender's Game